Teenage childbearing in Latin American countries (2002)
In spite of the rapid fertility transition experienced by most LAC countries, teenage fertility has not changed at the same pace or direction. Given early childbearing is deleterious for both mother and child, we describe the differentials in the levels and trends in teenage childbearing and analyze its proximate and socioeconomic determinants. We used DHS data from six LAC countries, Bolivia, Brazil, Colombia, Guatemala, Dominican Republic and Peru, for which there is available data for the second half of the 90's. Teenage fertility trends indicate different patterns of change across countries by area of residence. However, in most countries teenage fertility has increased in rural areas but has declined or remained constant in urban areas. Different contributions of marriage, proper use of family planning methods, and premarital births to teenage fertility behavior are reflected in differentials in unmarried parenthood across countries. Socioeconomic determinants are analyzed through: simple logit model, multilevel analysis, and continuous-time hazard rate models. These analyzes improve on prior research on LAC countries by: including contextual/regional factors, by isolating the effects into differentials in sexual activity and rates of childbearing, and by comparing the socioeconomic determinants of the timing of first birth and premarital birth. This research demonstrates that the effect of socioeconomic variables on the rate of childbearing can act through the timing of initial sexual intercourse (such as education, socioeconomic conditions of the households and area or residence) or through the timing of first birth (such as socialization in a female-headed family, availability/acceptability/use of family planning, and regional/country conditions - cultural and inherent characteristics).